Iran Diabetes Research Roadmap (IDRR) Study; Trends of Basic Sciences Publication: A Review Article - Saeedeh SAEEDI; Fatemeh BANDARIAN; Reza MESHKANI; Mitra NOURBAKHSH; Ensieh NASLI-ESFAHANI; Bagher LARIJANI (Tehran University of Medical Sciences, 2017)
Background: Basic science studies evaluation is important feature for an effective implementation of diabetes research and funding policy. This study aimed to provide an evaluation of diabetes basic research output up to 2015 in Iran. Methods: Data were retrieved from scientific search engine including PubMed, Web of science, SCOPUS as well as Iranian science databases including SID, IranMedex, and Magiran using "Diabetes mellitus" and 'Iran" keywords. After classification of total collected publications, basic sciences category was considered as one of the main groups. Specific areas of research activity in the main basic sciences disciplines, methodology of publications as well as proportionality of publications to WHO and Australian classification were identified. Results: Overall, 1249 basic science items were published up to 2015 in Iran. The greatest number of outputs were published in 2013 (n=201). The annual average growth rate was 38.45%. The Biochemistry contributed 63.7% to the overall output, followed by the Physiology (15.9%) and Histopathology & Anatomy (14.5%). The least participation was attributed to basic microbiology (1%). Animal study was the most common method (64%) followed by the Case-Control method (10.6%). Conclusion: The present study is the first large-scale analysis of Iranian basic researches in the field of diabetes. It identified single areas of research heavily focused or have been neglected. These areas should be reconsidered aiming to close the knowledge gaps and good policymaking. Basic researches and clinical relevance are approached based on old theories with slight originality in our country.